THE MODEL IMPLEMENTASI INOVASI BIROKRASI Studi Pada Program Raskin Pola Padat Karya Pangan di Kab.Timor Tengah Utara - Tri Anggraini (Politeknik STIA LAN Makassar, 2020)
Public Service Innovations in various sectors become a bridge for meeting the needs of excellent public services for the community in accordance with the mandate of the 1945 Constitution, Fulfilling the needs of public services is part of an effort to resolve problems in people's lives. One of them is the POLA PKP Raskin Innovation Program, which is an innovation program for the development of the agricultural sector in the North Middle East District. This innovation that has received the TOP 99 award The best innovation in Indonesia has in fact brought many benefits to the beneficiaries so that this innovation continues to be developed and refined in the hope that it can be carried out in a sustainable manner. Therefore this study aims to analyze the process of implementing the Raskin Innovation Program for the POLA PKP. The method used in this research is descriptive qualitative method of observation and in-depth interviews. The results showed that this innovation was carried out in three stages, Idea Generation (generation) consisting of Identification of Needs / Problems, Data Collection, Data Verification, Describing Conditions (objectives) expected Development and Formation of Ideas. The second stage is acceptance which consists of embracing (socialization / advocacy), building partnerships, building stakeholder commitment and making the next decision in the final stage is the implementation of gathering resources, placement of human resources, technical / mechanism training from sub-district to village as well as Monitoring and Evaluation.